Innovative research and applications in next-generation high performance computing - Hassan, Qusay F. 1982- (Advances in systems analysis, software engineering and high performance computing (ASASEHPC) book series, 2016)
This book addresses the future challenges, advances, and applications of high-performance computing and related technologies, demonstrating new ways to optimize the performance of these supercomputers